MicroRNA‐302c modulates peritoneal dialysis‐associated fibrosis by targeting connective tissue growth factor. Issue 4 (28th January 2019) - Li, Xiejia; Liu, Hong; Sun, Lin; Zhou, Xun; Yuan, Xinke; Chen, Yusa; Liu, Fuyou; Liu, Yu; Xiao, Li
Abstract: Long‐term peritoneal dialysis (PD) can lead to the induction of mesothelial/epithelial‐mesenchymal transition (MMT/EMT) and fibrosis; these effects eventually result in ultrafiltration failure and the discontinuation of PD. MicroRNA‐302c (miR‐302c) is believed to be involved in regulating tumour cell growth and metastasis by suppressing MMT, but the effect of miR‐302c on MMT in the context of PD is unknown. MiR‐302c levels were measured in mesothelial cells isolated from the PD effluents of continuous ambulatory peritoneal dialysis patients. After miR‐302c overexpression using lentivirus, human peritoneal mesothelial cell line (HMrSV5) and PD mouse peritoneum were treated with TGF‐β1 or high glucose peritoneal dialysate respectively. MiR‐302c expression level and MMT‐related factors alteration were observed. In addition, fibrosis of PD mouse peritoneum was alleviated by miR‐302c overexpression. Furthermore, the expression of connective tissue growth factor (CTGF) was negatively related by miR‐302c, and LV‐miR‐302c reversed the up‐regulation of CTGF induced by TGF‐β1. These data suggest that there is a novel TGF‐β1/miR‐302c/CTGF pathway that plays a significant role in the process of MMT and fibrosis during PD. MiR‐302c might be a potential biomarker for peritoneal fibrosis and a novel therapeutic target for protection against peritoneal fibrosis in PD patients.